Gender and Racial Gaps in Support for Policing and Correctional Reforms: are the Gaps a Consequence of Political Partisanship? - Hansen, Michael (Crime & delinquency, 2023)
Divisive criminal justice issues are typically framed through gender and racial lenses, with little empirical work considering the increasing role of political partisanship. Using the 2016 Cooperative Congressional Election Study (N = 55,000), we estimate multivariate models of support for four policing and correctional reforms. The models initially point to gender gaps and racial gaps. However, as with many public policy issues, support for criminal justice reforms are largely a product of political partisanship—the gender and racial gaps are largely a consequence of gender and racial gaps in partisanship and appear to be driven by white Republican men. As legislative bodies continue to be overrepresented with individuals with the same demographic profile, criminal justice reform prospects are limited.